The effect of neurofitness on correcting the psychoemotional state of students - Sharonova, A.V.; Yarchikovskaya, L.V.; Mironova, O.V.; Oshina, O.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to reveal the effectiveness of including neurofitness in the daily physical activity of students to correct their psycho-emotional state. Methods and structure of the study. During the study, surveys and questionnaires were conducted, in which 1324 first-year students participated. The control group (CG, n=15) and the experimental group (EG, n=15) included students from St. Petersburg State University. Results and conclusions. Analysis of the results revealed that more than 43% of first-year students experience psycho-emotional stress, and factors influencing the development of stress states were also identified. The authors proposed a method for incorporating neurofitness into students' daily physical activity to correct their psycho-emotional state, based on block grouping of specially selected exercises for the purposes of each section. The study found that improvements in the EG averaged 24.7%, while in the CG they averaged only 7.3%.